Alumni Monitoring and Supporting Model: A holistic view of quality management in higher education - Garzón Castrillón, Ana (2018)
The universities have among their responsibilities, providing high quality education that benefits students, alumni, organizations and society in general.Alumni monitoring becomes an important source for curriculum feedback, assessing the quality of the training and their consistency with the requirements for professional performance in different companies. However, there are many difficulties in establishing and maintaining a relationship of mutual benefits between educational institutions and their alumni. In this article, a Model for Alumni Monitoring and Supporting is presented. The model was designed from a holistic, ensuring that all involved actors get benefits. The model has been validated and can be adopted and/or adapted by educational institutions to create or strengthen the relationship with their alumni.